SELF ESTEEM LEVEL IN URBAN VOLLEYBALL PLAYERS OF SINDH, PAKISTAN - Shireen Bhatti; Syed Asim Hussain (The Sky, 2019)
Self-esteem has earned much interest which is believed to be an important construct for athlete to be able to perform during competition however it is the most crucial and influencing factor contributing to the success or failure of an athlete. The present research explored the aforementioned factor, which influences the performance of volleyball players. The study explored through survey and interview. To triangulate the data, volleyball players of urban areas of Sindh province were interviewed using Rosenberg self-esteem scale. Players were asked to rank various factors that affected their self-esteem. The study was conducted in Hyderabad, Karachi and Mirpurkhaas.The participants were 200 in number. All participants were players of volleyball game only, ranged from 16 to 20 years. The findings indicated that the selfesteem was witnessed low in volleyball players at public colleges. Results from this study suggest that coaches and sport psychology consultants to understand, prepare, and devise and implement, more effective strategies in order to help volleyball players in heightening self-esteem.